Український гельсінкський рух на тлі опозиційної боротьби в країнах Центрально-Східної Європи (1976-1991 рр.) (Zaporizhzhia Historical Review, 2021)
The article is devoted to comparative analysis of Ukrainian Helsinki Movement presented by Ukrainian Helsinki Group (1976-1987) and Ukrainian Helsinki Union (1988-1991), with similar movements in Czechoslovakia (“Charter 77”), Bulgaria (“Declaration 78”) and Romania. The following problems are examined in the article: numeral and qualitative organization membership; correlation of human rights and national component; ideological and political discussions inside the organizations; reaction of the authorities on the activities of Helsinki groups; the influence of Helsinki movement on the process of political elite’s transit in 1989-1991.